An autonomous switch based on a rotating magnet driven by magnetic launchers. (20th January 2021) - Boisseau, Sebastien; Tosoni, Olivier; Delette, Gerard; Alessandri, Baptiste; Boucaud, Matthieu; Bohnke, Marc; Despesse, Ghislain; Cellier, Christophe; Rannou, Fabien; Baeza, Alexandre; Perrot, Alexandre; Daccord, Marcel; et al.
Abstract: This paper reports on an innovative electromagnetic energy harvester for autonomous switches relying on a rotating magnet driven by magnetic launchers, and combined with a ferromagnetic circuit and a coil to turn the variation of magnetic flux induced by the rotating magnet into electricity. The device is able to operate on forward and backward translation movements. The energy harvester has been modeled, optimized, manufactured, characterized and integrated into a mechanical actuation system to form a complete autonomous switch that will be commercially available. The experimental output energy reaches 1.235 mJ (350 µ J cm −3 ) which is among the highest output energies and energy densities reached on autonomous switches in the state of the art. The electromechanical conversion efficiency is 56%, which is excellent for an energy harvester, and obtained thanks to the topology chosen for the electromagnetic converter. The energy harvester is finally connected to a diode-bridge-capacitor circuit to supply the RF emission of the commands with a Zigbee Green Power ® transmitter.